2014
DOI: 10.1007/s40167-014-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrating culture-as-situated-cognition and neuroscience prediction models

Abstract: The interface of mind, brain, culture, and behavior has provided rich ground for speculation, theorizing and empirical research. To date, theorizing has focused on between-country difference and much research has focused on quasiexperimental design in which groups are compared and the reasons for found differences imputed to be about the culture-brain interface. The authors of this paper argue for a somewhat different approach. We conceptualize culture as a set of human universals that are dynamically triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 98 publications
(139 reference statements)
0
25
0
Order By: Relevance
“…Prediction models demonstrate that neural activity tracks the task at hand: match between unfolding experience and prediction can increase higher-level neural activity while decreasing lowerlevel neural activity (Bar, 2009;Friston & Stephan, 2007). This neural response should be the case for cultural expertise as well (for a review, see Oyserman, Novin, Flinkenflögel, & Krabbendam, 2014). That is, cultural expertise should yield tight implicit predictions and shift cortical function if mismatch between unfolding experience and implicit prediction occurs.…”
Section: Making Predictions About and In The World Neural Prediction mentioning
confidence: 99%
“…Prediction models demonstrate that neural activity tracks the task at hand: match between unfolding experience and prediction can increase higher-level neural activity while decreasing lowerlevel neural activity (Bar, 2009;Friston & Stephan, 2007). This neural response should be the case for cultural expertise as well (for a review, see Oyserman, Novin, Flinkenflögel, & Krabbendam, 2014). That is, cultural expertise should yield tight implicit predictions and shift cortical function if mismatch between unfolding experience and implicit prediction occurs.…”
Section: Making Predictions About and In The World Neural Prediction mentioning
confidence: 99%
“…In contrast, males, but not females showed less prosocial behavior in decisions which were taken after deliberate processing compared to more spontaneous decisions (Espinosa and Kovářík, 2015). However, studies comparing either cultural or gender groups cannot address the underlying mechanisms for why differences are found (Oyserman, 2011; Oyserman et al, 2014). Rather than comparing groups that are supposed to differ in self-construal, or measuring individuals' trait self-construal and relating that to their decision-making, a more direct approach is to use priming methods to induce interdependent or independent mindsets and investigate the downstream consequences on fairness considerations in the Ultimatum Game.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the participants who were in the individualism-primed condition were more likely to make perspective-taking mistakes–by moving the wrong object–than the participants in the collectivism-primed condition. In the present research, we took a further step by using cultural primes rather than country primes to ensure that what is primed are universal individualistic and collectivistic concepts, which can be made accessible in all people, instead of culture-specific aspects only accessible to a particular culture or country [ 51 , 52 ]. In addition, we aimed to complement previous research by using a comprehensive ToM task.…”
Section: Introductionmentioning
confidence: 99%